Evaluation of strawberry cultivars as sources of high winter hardiness and productivity - M. I. Zubkova; S. D. Knyazev; Z. E. Ozherelieva (Труды по прикладной ботанике, генетике и селекции)
Background. The realization of high productivity potential in strawberry plants significantly depends on their adaptability to soil and climate conditions of their cultivation. Winter hardiness is the most important trait in the central part of Russia. With this in view, the purpose of this study was to identify sources of high winter hardiness combined with high productivity and yield potential among the studied cultivars.Materials and methods. The research was carried out at the primary variety testing site of the All-Russian Research Institute of Fruit Crop Breeding (VNIISPK), Orel Province, in accordance with the published program and methodology of fruit, berry and nut variety studies. The testing covered 23 domestic and foreign strawberry cultivars. An Espec PSL-2KPH climate chamber (Japan) and a Polair refrigerator cabinet (Russia) were used for artificial freezing.Results. Winter hardiness of strawberry cultivars was assessed under artificial freezing conditions. Cvs. ‘Korona’, ‘Tsaritsa’, ‘Solovushka’ and ‘Sara’ were the most winter-hardy cultivars. The study of the cultivars in the field made it possible to identify the most productive and large-fruited ones: ‘Alba’, ‘Azia’, ‘Bereginya’ and ‘Tsaritsa’. Cv. ‘Tsaritsa’ combines high winter hardiness and high yield productivity and yield potential, being a valuable source of these traits in breeding practice. According to a set of indicators ‘Tsaritsa’ is promising for large-scale cultivation in the Central Black Earth Region of Russia.